Konsep Pendidikan Ki Hadjar Dewantara Dalam Penanaman Nilai-Nilai Multikultural Untuk Siswa Sekolah Dasar - Dewi Nancy Shabartini; Sholeh Hidayat; Ujang Jamaludin; Suroso Mukti Leksono (Elementary Teacher Education Program, Majalengka University, 2023)
In line with the development of science and technology, the Indonesian nation's education began to lose its identity. Indonesian education seems to be tossing and turning, not having clear directions and goals where to go and tends to imitate a lot from the education system in other countries. Therefore, this study aims to describe how the education system created by Kıe Hadjar Dewantara is dissecting in an effort to restore national identity through education based on cultural values. This study used a qualitative approach with a descriptive analysis design. Indonesian strength becomes an energy in shaping Indonesia as a great nation. A great nation is realized through a strong human character. If national values are not continuously instilled, it will have the potential to become a capital of division and conflict against a nation. Therefore, multicultural education places great emphasis on the importance of accommodating the rights of every culture and society to maintain and maintain national cultural and community identity. So that later the Indonesian people will have good character and be a respectable nation.